Awareness, performance, and practices an exploration of the strategies and challenges in implementing the ecological solid waste management program in secondary schools of Tacloban City - Molina, Sheena Aira E.
This study investigated the level of awareness, implementation, performance, practices, strategies, and challenges in the Ecological Solid Waste Management Program (ESWMP) among secondary schools in Tacloban City. Despite the existence of Republic Act No. 9003 and Republic Act No. 9512, a notable research gap persists regarding how these policies are understood and applied at the school level, particularly in disaster-prone urban areas like Tacloban. Addressing this gap, the study utilized a mixed-methods approach, involving 297 respondents composed of secondary school teachers and school heads. Quantitative data were gathered through survey questionnaires, while qualitative responses provided deeper insight into school practices, strategies and challenges. Findings revealed a high level of awareness of ESWM policies among respondents. However, implementation and performance levels were found to be moderate, indicating a disconnect between awareness and actual practice. Statistical analysis showed a significant positive correlation between awareness, implementation, and performance, underscoring the importance of translating knowledge into actionable programs. Thematic analysis further highlighted school-based practices such as waste segregation, MRF establishment, student-led initiatives, and creative recycling projects. Strategies included education campaigns, incentive programs, and community engagement. Key challenges involved resource limitations, weak policy enforcement, and inconsistent stakeholder participation. The findings suggest the need for stronger institutional support, capacity building, and curriculum integration of ESWM principles. These are essential to fostering a sustainable environmental culture in schools. This research provides valuable insights for policymakers, school administrators, and educators aiming to strengthen the operationalization of environmental policies in the educational sector.